Identification of an elite core panel as a key breeding resource to accelerate the rate of genetic improvement for irrigated rice - Juma, Roselyne U.; Bartholomé, Jérôme; Thathapalli Prakash, Parthiban; Hussain, Waseem; Platten, John D.; Lopena, Vitaliano; Verdeprado, Holden; Murori, Rosemary; Ndayiragije, Alexis; Katiyar, Sanjay Kumar; Islam, Md. Rafiqul; Biswas, Partha S.; et al. (Springer, 2021)
Rice genetic improvement is a key component of achieving and maintaining food security in Asia and Africa in the face of growing populations and climate change. In this effort, the International Rice Research Institute (IRRI) continues to play a critical role in creating and disseminating rice varieties with higher productivity. Due to increasing demand for rice, especially in Africa, there is a strong need to accelerate the rate of genetic improvement for grain yield. In an effort to identify and characterize the elite breeding pool of IRRI’s irrigated rice breeding program, we analyzed 102 historical yield trials conducted in the Philippines during the period 2012–2016 and representing 15,286 breeding lines (including released varieties). A mixed model approach based on the pedigree relationship matrix was used to estimate breeding values for grain yield, which ranged from 2.12 to 6.27 t·ha−1. The rate of genetic gain for grain yield was estimated at 8.75 kg·ha−1 year−1(0.23%) for crosses made in the period from 1964 to 2014. Reducing the data to only IRRI released varieties, the rate doubled to 17.36 kg·ha−1 year−1(0.46%). Regressed against breeding cycle the rate of gain for grain yield was 185 kg·ha−1 cycle−1(4.95%). We selected 72 top performing lines based on breeding values for grain yield to create an elite core panel (ECP) representing the genetic diversity in the breeding program with the highest heritable yield values from which new products can be derived. The ECP closely aligns with the indica 1B sub-group ofOryza sativathat includes most modern varieties for irrigated systems. Agronomic performance of the ECP under multiple environments in Asia and Africa confirmed its high yield potential. We found that the rate of genetic gain for grain yield found in this study was limited primarily by long cycle times and the direct introduction of non-improved material into the elite pool. Consequently, the current breeding scheme for irrigated rice at IRRI is based on rapid recurrent selection among highly elite lines. In this context, the ECP constitutes an important resource for IRRI and NAREs breeders to carefully characterize and manage that elite diversity.